ANALISIS PENGARUH FDR, CAR, NPF, DAN BOPO TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA (STUDI KASUS BANK SYARIAH MANDIRI PERIODE 2016-2020) - Meiske Wenno (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
AbstractThe purpose this article is to determine the effect of the influence of Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Operating Expenses and Operating Income (BOPO) on the Profitability of Islamic Banks in Indonesia (Case Study of Islamic Banks). Independent Period 2016-2020). The sample of this research is Bank Syariah Mandiri. Analysis of the data used to test the hypothesis is to use multiple regression analysis techniques. The findings of this study are that the Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) has no effect on ROA, while the ratio of Operating Expenses and Operating Income (BOPO) has an effect on ROA. The managerial implication of this research is to encourage the bank's management to set a strategy to maximize its profitability by considering the capital adequacy ratio, financing risk and liquidity risk. Keywords – FDR, CAR NPF, BOPO